Influence of non-synonymous sequence mutations on the architecture of HIV-1 clade C protease receptor site : docking and molecular dynamics studies - Onywera, David Harris (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Despite the current interventions to avert contagions and AIDS-related deaths, sub-Saharan Africa is still the region most severely affected by the HIV/AIDS pandemic, where clade C is the dominant circulating HIV-1 strain. The pol-encoded HIV-1 protease enzyme has been extensively exploited as a drug target. Protease inhibitors have been engineered within the framework of clade B, the commonest in America, Europe and Australia. Recent studies have attested the existence of sequence and catalytic disparities between clades B and C proteases that could upset drug susceptibilities. Emergence of drug-resistant associated mutations and combinatorial explosions due to recombination thwarts the attempt to stabilize the current highly active antiretroviral therapy (HAART) baseline. The project aimed at identifying the structural and molecular mechanisms hired by mutants to affect the efficacies of both FDA approved and Rhodes University (RU)-synthesized inhibitors, in order to define how current and or future drugs ought to be modified or synthesized with the intent of combating drug resistance. The rationale involved the generation of homology models of the HIV-1 sequences from the South African infants failing treatment with two protease inhibitors: lopinavir and ritonavir (as monitored by alterations in surrogate markers: CD4 cell count decline and viral load upsurge). Consistent with previous studies, we established nine polymorphisms: 12S, 15V, 19I, 36I, 41K, 63P, 69K, 89M, and 93L, linked to subtype C wild-type; some of which are associated with protease treatment in clade B. Even though we predicted two occurrence patterns of M46I, I54V and V82A mutations as V82A→I54V→M46I and I54V→V82A→M46V, other possibilities might exist. Mutations either caused a protracted or contracted active site cleft, which enforced differential drug responses. The in silico docking indicated susceptibility discordances between clades B and C in certain polymorphisms and non-polymorphisms. The RU-synthesized ligands displayed varied efficacies that were below those of the FDA approved protease inhibitors. The flaps underwent a wide range of structural motions to accommodate and stabilize the ligands. Computational analyses unravelled the need for these potential drugs to be restructured by (de novo) drug engineers to improve their binding fits, affinities, energies and interactions with multiple key protease residues in order to target resilient HIV-1 assemblages. Accumulating evidences on contrasting drug-choice interpretations from the Stanford HIVdb should act as an impetus for the customization of a HIVdb for the sub-Saharan subcontinent.
Keywords: HIV (Viruses) -- Research; HIV infections -- Treatment -- Research; HIV infections -- Chemotherapy; Protease inhibitors -- Research; Viruses -- Effect of drugs on -- Research; Antiretroviral agents